Efficacy and Safety of Axicabtagene Ciloleucel and Tisagenlecleucel Administration in Lymphoma Patients With Secondary CNS Involvement: A Systematic Review - Wu, XiaoQin; Zhang, XinYue; Xun, RenDe; Liu, MengSi; Sun, Zhen; Huang, JianChao (Frontiers in Immunology, 2021)
Background: the efficacy and safety of chimeric antigen receptor T (CAR-T) cell therapy in the treatment of non-Hodgkin’s lymphoma has already been demonstrated. However, patients with a history of/active secondary central nervous system (CNS) lymphoma were excluded from the licensing trials conducted on two widely used CAR-T cell products, Axicabtagene ciloleucel (Axi-cel) and Tisagenlecleucel (Tisa-cel). Hence, the objective of the present review was to assess whether secondary CNS lymphoma patients would derive a benefit from Axi-cel or Tisa-cel therapy, while maintaining controllable safety. Method: two reviewers searched PubMed, Embase, Web of Science, and Cochrane library independently in order to identify all records associated with Axi-cel and Tisa-cel published prior to February 15, 2021. Studies that included secondary CNS lymphoma patients treated with Axi-cel and Tisa-cel and reported or could be inferred efficacy and safety endpoints of secondary CNS lymphoma patients were included. A tool designed specifically to evaluate the risk of bias in case series and reports and the ROBINS-I tool applied for cohort studies were used. Results: ten studies involving forty-four patients were included. Of these, seven were case reports or series. The other three reports were cohort studies involving twenty-five patients. Current evidence indicates that secondary CNS lymphoma patients could achieve long-term remission following Axi-cel and Tisa-cel treatment. Compared with the non-CNS cohort, however, progression-free survival and overall survival tended to be shorter. This was possibly due to the relatively small size of the CNS cohort. The incidence and grades of adverse effects in secondary CNS lymphoma patients resembled those in the non-CNS cohort. No incidences of CAR-T cell-related deaths were reported. Nevertheless, the small sample size introduced a high risk of bias and prevented the identification of specific patients who may have derived a benefit from CAR-T cell therapy. Conclusion: secondary CNS lymphoma patients could seem to benefit from both Axi-cel and Tisa-cel treatment, with controllable risks. Thus, CAR-T cell therapy shows potential as a candidate treatment for lymphoma patients with CNS involvement. Further prospective studies with larger samples and longer follow-up periods are warranted and recommended.